REACTIVE ARTHRITIS - B. S. Belov; S. V. Shubin; R. M. Balabanova; Sh. F. Erdes (Научно-практическая ревматология)
At present, the problem of reactive arthritis (ReA) remains relevant in rheumatology. This is due to rather high prevalence of the disease primarily in Russia, which cannot but alarm. Analysis of epidemiological findings suggests a number of possible explanations for variability of ReA incidence rates in some regions of the Russian Federation and other countries. The lecture details the clinical presentations of the disease and analyzes the significance of different laboratory procedures aimed at detecting the pathogen of ReA. It presents Russian diagnostic criteria for ReA. It also sets forth basic approaches to ReA therapy with emphasis on the use of antimicrobial drugs. The efficiency and safety of drug immunomodulation (interferon inducers, polyoxidonium, immunofan, etc.) in treating urogenital Chlamydia infection in ReA patients are not confirmed by the data of randomized controlled trials. In this connection, it is impossible to give any recommendations for their use in urogenic ReA.